Photocatalytic Studies of MgO Nano Powder; Synthesized by Green Mediated Route. (2018) - Anil Kumar, M.R.; Mahendra, B.; Nagaswarupa, H.P.; Surendra, B.S.; Ravikumar, C.R.; Shetty, Krushitha
Abstract: MgO nano powders were synthesized by a bio mediated route. The obtained products were characterized by powder X-ray diffraction (PXRD), diffuse reflectance spectroscopy (DRS) Scanning electron microscope (SEM), Transmissionelectron Microscope (TEM) and Fourier transform infrared spectroscopy (FTIR). PXRD patterns show hexagonal single cubic phase MgO matched with JCPDS Card No 78-0430. The crystallite size obtained from TEM was found to be ∼ 15-20 SEM result reveals porous nature of the obtained nano-powder. The optical energy gap is 3.20eV which demonstrates that there is a movement to the higher wavelengths of the absorption edge with reduction of the energy gap when using green fuel for synthesis. The photocatalytic studies relatively high activity for degradation of Malachite Green (MG) and Rhodamine-B (Rh-B) under sunlight irradiation compared to UV light. The good structure and excellent performance of ZnO nano-composites, suggest its promising application in dye decolarization